From old tricks to Netflix: How local are interlingual subtitling norms for streamed television? - Pedersen, Jan (Journal of Audiovisual Translation, 2018)
Like other translation norms, interlingual subtitling norms for television evolve over time, influenced by technology, mediascape development and other trends. Originating in cinema subtitling norms, TV subtitling norms began to develop at national public service broadcasters. Later, norms became international with the rise of the DVD and the proliferation of commercial TV in Europe. These days, the most influential force driving subtitling norms is arguably the global video on demand (VOD) providers. This paper investigates the subtitling guidelines of VOD giant Netflix, in search of the question: How local are interlingual subtitling norms for streamed television? The results show that there is little variation in the initial guidelines, but that they are continually becoming more varied, as they are localized using input from users.